1996
DOI: 10.1063/1.361141
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rapid thermal annealing and internal gettering on Czochralski-grown silicon. I. Oxygen precipitation

Abstract: Influence of rapid thermal annealing and internal gettering on Czochralskigrown silicon. II. Light beam induced current study of recombination centers Charged particle activation analysis study of the oxygen outdiffusion from Czochralskigrown silicon during classical and rapid thermal annealing in various gas ambient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
7
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
3
7
0
Order By: Relevance
“…With increasing RTA temperature the precipitates become more spherical. This is in agreement with results reported by Maddalon-Vinante et al (17). They have found by FTIR measurements that during thermal treatment after a preceding RTA spherical instead of plate-like precipitates are formed which are not suitable to getter Cr (17,18).…”
Section: Ecs Transactions 25 (3) 67-78 (2009)supporting
confidence: 93%
“…With increasing RTA temperature the precipitates become more spherical. This is in agreement with results reported by Maddalon-Vinante et al (17). They have found by FTIR measurements that during thermal treatment after a preceding RTA spherical instead of plate-like precipitates are formed which are not suitable to getter Cr (17,18).…”
Section: Ecs Transactions 25 (3) 67-78 (2009)supporting
confidence: 93%
“…4, it can be concluded that for higher the RTA temperature the precipitates become increasingly spherical. This result is well in agreement with the results of Maddalon-Vinante et al (5). They have found by FTIR measurements that during thermal treatment after a preceding RTA spherical instead of plate-like precipitates are formed which are not suitable to getter Cr.…”
Section: Ecs Transactions 18 (1) 995-1000 (2009)supporting
confidence: 93%
“…On the one hand, vacancies built into the growing precipitates can reduce the lattice strain which is due to the different molecular volume of silicon and silicon oxide. On the other hand, it was reported that the getter efficiency of precipitates for chromium in RTA pre-treated wafers is decreased (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…3 The getter efficiency of oxygen precipitates depends on their density and morphology. 4,5 The density of the precipitates can be controlled by the temperature of RTA and it can be easily determined by preferential etching. The morphology of oxygen precipitates depends on the type and the concentration of dopants, the thermal history, and the annealing temperature and time.…”
mentioning
confidence: 99%